External Sector Gender Wage Gaps in Sri Lanka: An Analysis Using Matching Techniques - Sasini T. K Kulatunga (Economy for All, 2021)
This study explores the differences in external sector wages between matched sets of men and women by applying the propensity score matching (PSM) technique and the matching method proposed by \~Nopo (2008). The data for this study comes from Sri Lanka's Labor Force Surveys for the years, 2015 and 2018. Despite matching for human capital difference, occupations, occupational hierarchies, demographic differences, family and household characteristics, significant gender gaps remain in the export income earning sectors of the Sri Lankan economy. Compared to 2015, the unexplained gap has increased in 2018 . In the wage distributions (after matching), the peak of the unexplained wage gap seems to have shifted from the low-income deciles in 2015, to 5th and 6th deciles in 2018, indicating possible wage adjustments at the entry and low-income categories and neglect of such adjustment at middle-income levels. Using \~Nopo's (2008) non-parametric matching technique with sectorial and intersectional variables , this study also shows that the tea and apparel export sectors record the widest wage inequalities compared to the tourism sector. The ethnic Sinhala women encounter unexplained gender wage gaps in the tea export sector wherein Tamil and Muslim women are more akin to encounter such gaps in the apparel export sector. The findings of this study debunk existing mainstream narratives relating to gender wage differentials. Neither competition, sectorial expansion nor differences in male and female labor explains the wage gaps across matched sets of men and women. The patriarchal socioeconomic structures culpable for subjugation and gender manifesting as an input in capitalist production are plausible causes for the horizontal wage inequalities between men and women with similar socio-economic attributes.
Keywords: J16; J3; F41; 330; Export sector; Gender wage gaps; Sri Lanka